EFEKTIVITAS PELAKSANAAN PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA DIKOTA PEKANBARU - Ulfa Dadan Raya; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
In order to improve the quality of life and people's livelihoods through healthy, safe, harmonious and orderly housing and settlements, it is necessary to improve the quality of slum housing and slum settlements. The government has established a Self-Help Housing Stimulant Assistance through the Ministry of Public Housing. Based on Regulation of the Minister of Public Works and Public Housing Number 07 of 2018 concerning Self-Help Housing Stimulant Assistance, the Self-Help Housing Stimulant Assistance is a government facilitation in the form of stimulant assistance for low-income communities to develop / improve the quality of homes for low income communities. The phenomenon in this study is that the assistance provided is not yet on target. The purpose of this assessment is to find out how effective the implementation of self-help housing stimulant programs in the city of Pekanbaru and to determine the inhibiting factors of the program's effectiveness. This research was conducted at Pekanbaru City by using a qualitative descriptive method, the data were collected through observation and interviews.This research was conducted using effectiveness theory by Makmur, which consists of timeliness, cost calculation, measurement, accuracy in making choices, the accuracy of thinking, the accuracy of carrying out orders, the accuracy of determining goals and the accuracy of the target. The conclusion of this study is that the implementation of the Self-Help Housing Stimulant Assistance program at Pekanbaru City has not been carried out effectively. This is indicated by the fact that there are still many people who receive self-help housing assistance who complain about the implementation of program. This happens because the efforts made in the process of implementing the program are not optimal in terms of supervision and authority. Keywords : Effectiveness, Implementation, Self-Help House